Suggestions for formative assessment system construction of the "internet+" new teaching mode and its application in an evidence-based medicine course - Yun-Yun WANG; Yu WANG; Di HUANG; Si-Yu YAN; Qiao HUANG; Sheng LI; Xian-Tao ZENG; Ying-Hui JIN (Yixue xinzhi zazhi)
"Internet +" has had a great impact on education and teaching. The organization of new teaching activities integrated into information technology has gradually been normalized, bringing in-creased openness, autonomy and flexibility. Methods of strengthening the supervision, management and evaluation of curriculum teaching activities are cited as one of the difficulties of promoting teaching re-form. Formative assessment plays an important role in the process of "teaching, feedback and improve-ment” as being one of the important ways of teaching evaluation. This paper analyzes the characteristics of the “Internet+ teaching” and its formative evaluation system in medical education, and proposes the construction of an evaluation system and the focus of reform. Meanwhile, combined with the teaching experience of the blended learning of evidence-based medicine in Wuhan University, taking that course as an example, this paper proposes ideas for development of a formative evaluation system to promote peer discussion, jointly promote the deep integration of information technology with the evidence-based medicine course, and help to cultivate medical students' ability in evidence-based medicine.